Pemanfaatan Limbah Kulit Kakao Sebagai Pupuk Organik - Haderiah, Haderiah; La Taha, La Taha; Rahayu, Sri (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Cocoa peel waste is a byproduct of cocoa fruit processing that is quite abundant and has not been optimally utilized. Therefore, an action is needed that can utilize cocoa shell waste into something useful, one of which is made into organic fertilizer so that it can overcome the problem that has been one of the causes of environmental pollution in the plantation area. This study aims to determine the utilization of cocoa shell waste as organic fertilizer. The type of research used in this study is a quasi-experiment with the aim of knowing the length of composting time and the quality of the C/N Ratio. The results showed that the utilization of cocoa shell waste with the addition of leachate activator at a dose of 200 ml occurred for 18 days with a C/N Ratio value of 11, the addition of leachate activator at a dose of 250 ml occurred for 16 days with a C/N Ratio value of 13, the addition of leachate activator at a dose of 300 ml occurred for 14 days with a C/N Ratio value of 12 and without the addition of activator occurred for 28 days with a C/N Ratio value of 15. This shows that the addition of leachate activator is able to accelerate the composting process compared to without using leachate activator. The conclusion of this research is that the utilization of cocoa shell waste with the addition of leachate water activator with doses of 200 ml, 250 ml and 300 ml on the length of composting time and C/N Ratio value meets the requirements or quality standards set by SNI 19-7030-2004. Keywords : Organic Fertilizer, Cocoa Shell Waste, Cow Manure, Bran, Leachate Water